The notorious Ben Hecht : iconoclastic writer and militant Zionist - Gorbach, Julien, 1969- (Purdue University Press, 2019)
"The Notorious Ben Hecht: Iconoclastic Writer and Militant Zionist is a biography of a great twentieth century writer that treats his activism during the 1940s as the central drama of his life. It details the story of how Hecht earned admiration as a humanitarian and vilification as an extremist at this pivotal moment in history, about the origins of his beliefs in his varied experiences in American media, and about the consequences. Who else but Hecht could have drawn the admiration of Ezra Pound, clowned around with Harpo Marx, written Notorious! and Spellbound with Alfred Hitchcock, launched Marlon Brando's career, ghosted Marilyn Monroe's memoirs, hosted Jack Kerouac and Salvador Dalí on his television talk show, and plotted revolt with Menachem Begin? Any lover of modern history who follows this journey through the worlds of gangsters, reporters, Jazz Age artists, Hollywood stars, movie moguls, political radicals, and guerrilla fighters will never look at the twentieth century in the same way again"--